Anion Exchange in Coordination‐Network Materials. Issue 27 (16th July 2013) - Phuengphai, Pongthipun; Massera, Chiara; Reedijk, Jan; Youngme, Sujittra; Gamez, Patrick
Abstract: Six coordination polymers, namely, the three‐dimensional frameworks {[Zn3 (4, 4′‐bpy)3.5 (μ‐O2 CH)4 (H2 O)2 ](ClO4 )2 (H2 O)2 } n (1, 4, 4′‐bpy = 4, 4′‐bipyridine) and {[Zn3 (4, 4′‐bpy)3.5 (μ‐O2 CH)4 (H2 O)2 ](PF6 )2 } n (2 ), the two‐dimensional networks {[Zn(4, 4′‐bpy)(μ‐O2 CH)(H2 O)2 ](CF3 SO3 )(H2 O)} n (3 ) and {[Zn3 (4, 4′‐bpy)4 (μ‐O2 CCH2 CH3 )4 ](ClO4 )2 (4, 4′‐bpy)2 (H2 O)4 } n (4 ), the one‐dimensional double‐stranded zigzag chain {[Zn3 (4, 4′‐bpy)4 (μ‐O2 CCH2 CH3 )4 (H2 O)2 ](PF6 )2 (H2 O)2 } n (5 ), and the one‐dimensional double‐ladder chain {[Zn2 (4, 4′‐bpy)2 (μ‐O2 CCH2 CH3 )2 (H2 O)2 ](CF3 SO3 )2 } n (6 ), have been prepared. The solid‐state structures of the six compounds all exhibit void spaces that contain anions and neutral guest molecules, namely, water for1, 3 and5, and water/4, 4′‐bpy for4 . The anion‐exchange properties of the compounds have been investigated by monitoring the substitution of the ions by infrared spectroscopy. Furthermore, X‐ray powder diffraction studies and elemental analyses have been used to further confirm the anion exchange. The results show that the anions in all compounds can be replaced with ClO4 – or PF6 – for1, 2, 4, and5, ClO4 – and PF6 – for3, and ClO4 –, PF6 –, and BF4 – for6 . Furthermore, compound1 shows interesting reversible anion‐exchange properties in aqueous solution. Abstract : A series of cationic extended coordination frameworks exhibits anion‐exchange properties for a variety of inorganic anionic species.